2001
DOI: 10.1002/mus.1184
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myopathy associated with mixed connective tissue disease and scleroderma renal crisis

Abstract: Mixed connective tissue disease is a rheumatological syndrome with neuromuscular manifestations that may include inflammatory myopathy and carpal tunnel syndrome. We report a patient who presented with an inflammatory myopathy and bilateral carpal tunnel syndrome prior to the diagnosis of a connective tissue disorder. Early in the course of treatment, a syndrome of acute renal failure developed. Knowledge of this syndrome, scleroderma renal crisis, and its possible relation to corticosteroid treatment is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…Therefore, steroids use, mild chronic hypertension, nonimmunologic mechanism of glomerulonephritis or vasculitis might have resulted in further loss of residual renal functions in our case. Like our case, in Greenberg and Amato's patient [22], SRC occurred following steroids use for myositis, resulting in dialysis-dependent chronic kidney disease. Therefore, patients with MCTD having scleroderma should be vigilantly screened for SRC by the regular monitoring of blood pressure and renal functions.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, steroids use, mild chronic hypertension, nonimmunologic mechanism of glomerulonephritis or vasculitis might have resulted in further loss of residual renal functions in our case. Like our case, in Greenberg and Amato's patient [22], SRC occurred following steroids use for myositis, resulting in dialysis-dependent chronic kidney disease. Therefore, patients with MCTD having scleroderma should be vigilantly screened for SRC by the regular monitoring of blood pressure and renal functions.…”
Section: Discussionsupporting
confidence: 59%
“…She responded to ACEi and prostaglandins [21]. Similarly, Greenberg and Amato et al reported a case of SRC in MCTD in a female patient with inflammatory myopathy who was started on high-dose steroids which precipitated SRC, leading to chronic kidney disease stage V. Two months following the SRC episode, she was still dialysis-dependent [22]. From the studies we gathered, there were a total of 11 MCTD patients with SRC, of which 3 became dialysis-dependent [4,13].…”
Section: Discussionmentioning
confidence: 92%
“…We record blood pressure at each visit as accelerated hypertension and renal failure may occur, particular in patients with scleroderma or mixed connective tissue disease and overlap myositis 55. Periodic eye examinations for cataracts and glaucoma should be performed.…”
Section: Treatmentmentioning
confidence: 99%
“…Recognizing the presence of overlapping conditions is important and may change management strategies. For example, high dose steroids are often avoided in patients with myositis-scleroderma overlap because of the risk of renal crisis (2). …”
Section: Introductionmentioning
confidence: 99%